Captação de recursos: planejamento, prática e resultados: um estudo em museus do Brasil - Becker, Ivani de Arruda (2003)
Changes that have taken place in the cultural policies of several countries have brought to the fore cultural discussions on the need to develop novel sources of resources and to establish new stances and strategies enabling the creation of partnerships between profit and non-profit entities. In Brazil, government initiatives, such as the launching of the foundation for a new policy on museums, are being accompanied by events such as the imminent suspension of Vitae’s activities, which suggests that this is the appropriate moment to debate broader changes, meaning museums should begin to adapt to the new reality that is emerging.